Program module using the procedure for the formation and verification of electronic digital signature - Ільєнко, А. В.; Ільєнко, С. С. (Science-based technologies, 2018)
In the article the research of modern theoretical bases of classification of algorithms of formation and verification of electronic digital signature is carried out. Based on the analysis and classification, it has been determined that, in general, all electronic signature schemes can be divided into two large classes by their structure: ordinary digital signatures (with the addition) and electronic digital signatures with message recovery. The studies conducted have made it possible to determine that the message recovery schemes differ from the schemes with the addition that they do not completely hash the messages, but instead use the masking and redundancy features of the message. It is also determined that according to the criterion of the problem underlying the formation and verification of an electronic digital signature, algorithms based on the problem of a discrete logarithm in the group of points of an elliptic curve will be most crypto-resistant. Also described is the approach to ensuring the integrity and confidentiality of EDS-based information on the basis of elliptic curves using the standard DSTU 4145-2002 and the Niemberg-Ruppel scheme, which enables the recovery of the message. The main difference was the replacement of the hash function with the hash token function, which makes the signature and verification procedure reversed and allows you to retrieve messages from the signature r-component. The software module for implementing digital signatures with the national standard DSTU 4145-2002 with ECNR algorithm based on the problem of discrete logarithm in the group of points of the elliptic curve is described and the effectiveness of the software implementation from the condition of securing confidentiality and integrity has been evaluated.